Enhancing Islamic Education Teachers’ AI Ethics Competence Through a Case-Based Training Module on Contemporary Fiqh Issues - Wiken Febrianti; Yeniarti Samaun; Yuniar (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study investigates the enhancement of Islamic Religious Education (PAI) teachers’ competence in Artificial Intelligence (AI) ethics through a case-based training module grounded in contemporary fiqh at MTsN 1 Baubau. The research responds to the growing ethical challenges posed by generative AI in education, including academic integrity risks, misinformation and bias, and concerns about data privacy. Employing a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study developed an operational training module integrating maqāṣid al-sharī‘ah, selected fiqh maxims (qawā‘id fiqhiyyah), and maṣlaḥah–mafsadah reasoning into case-based learning activities relevant to classroom practices. A qualitative case study orientation was embedded within the development process through needs assessment interviews, training observations, and document analysis, complemented by a one-group pretest–posttest design to examine effectiveness. Participants were PAI teachers at MTsN 1 Baubau who engaged in structured training sessions featuring guided case discussions, ethical decision-making simulations, and the production of practical outputs such as classroom AI-use policies and authentic assessment designs. Data analysis combined descriptive quantitative procedures (e.g., gain scores) with thematic analysis of participant reflections and observational notes to capture changes in knowledge, attitudes, and pedagogical skills. The findings indicate improvements in teachers’ operational understanding of AI ethics (attribution and disclosure, privacy precautions, bias verification, and integrity-focused assessment), a shift toward proactive ethical governance of AI use, and strengthened pedagogical capacity to translate ethical principles into classroom routines and assessment practices. Challenges included uneven digital literacy, limited time for follow-up implementation, and the need for madrasah-level policy alignment. Overall, the study suggests that integrating contemporary fiqh with case-based professional learning is a promising pathway for strengthening responsible AI use in PAI education.